Quantification of per- and polyfluoroalkyl substances (PFASs) in aqueous film-forming foam (AFFF)-impacted water: Comparisons between methodologies and laboratories - Chuhui Zhang; Nicholas Gonda; Ashley N. Kimble; Eric Redman; Cynthia M. Grim; Siwei Gu; Anthony Bednar; Karen Dahl; Chenyi Yuan; Yue Zhi; Hefa Cheng; Christopher P. Higgins (Journal of Hazardous Materials, 2025)

Recommendations for advancing test protocols examining the photo-induced toxicity of petroleum and polycyclic aromatic compounds - Matthew M. Alloy; Bryson E. Finch; Collin P. Ward; Aaron D. Redman; Adriana C. Bejarano; Mace G. Barron (Aquatic Toxicology, 2023)

New Diversity Arrays Technology (DArT) markers for tetraploid oat (Avena magna Murphy et Terrell) provide the first complete oat linkage map and markers linked to domestication genes from hexaploid A. sativa L. - R. E. Oliver; E. N. Jellen; G. Ladizinsky; A. B. Korol; A. Kilian; J. L. Beard; Z. Dumlupinar; N. H. Wisniewski-Morehead; E. Svedin; M. Coon; R. R. Redman; P. J. Maughan; et al. (Theoretical and Applied Genetics, 2011)

Effects of smoking abstinence on adult smokers with and without attention deficit hyperactivity disorder: results of a preliminary study - F. Joseph McClernon; Scott H. Kollins; Avery M. Lutz; David P. Fitzgerald; Desiree W. Murray; Christina Redman; Jed E. Rose (Psychopharmacology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Agrarian legacy in soil nutrient pools of urbanizing arid lands - DAVID BRUCE LEWIS; JASON P. KAYE; CORINNA GRIES; ANN P. KINZIG; CHARLES L. REDMAN (Global Change Biology, 2006)
Today's worldwide expansion of dry land cities consumes cultivated and native ecosystems, providing laboratories for investigating imprints of former land use in places where people now live. Around Phoenix, USA, we compared soil nutrient pools in residential yards converted from farms with nutrient pools in yards developed on native desert. Organic matter, carbon (C), nitrogen (N), and soluble ions were >2‐fold greater in yards that were previously agrarian than in yards that were not. These pools remain elevated 40 years after land conversion to residential use. Present N accumulation (1.5 g m −2 yr −1 ) is not affected by prior land use, suggesting that rates of residential fertilizer application and retention are not affected by antecedent soil fertility. Bioavailable, inorganic phosphorus (P av ) is elevated in soil with a recent agrarian past, but this signal disappears after 10–30 years of residential use owing to an accumulation of P av in never‐farmed yards. Our results indicate a ‘direct agrarian legacy,’ wherein agrarian amendment of nutrient pools endures urbanization, more so than an ‘indirect legacy,’ wherein present land management is molded by former land use. Agriculture in dry lands thus sequesters material in soils, and—as we also found higher material contents in residential soils than in contemporary agrarian soils—residential land use simply adds to the agrarian legacy these soils already bear. Intense human use of arid lands may cause increases in material pools in soils, a condition with potential global consequence.

Photoperiod regulates leptin sensitivity in field voles, Microtus agrestis - E. Król; J. S. Duncan; P. Redman; P. J. Morgan; J. G. Mercer; J. R. Speakman (Journal of Comparative Physiology B, 2006)

Breeding site choice fails to explain interannual associations of female grey seals - P. P. Pomeroy; P. R. Redman; S. J. S. Ruddell; C. D. Duck; S. D. Twiss (Behavioral Ecology and Sociobiology, 2005)

BEHAVIORAL EVIDENCE OF THERMAL STRESS FROM OVERHEATING IN UK BREEDING GRAY SEALS - S. D. Twiss; N. C. Wright; N. Dunstone; P. Redman; S. Moss; P. P. Pomeroy (Marine Mammal Science, 2002)
A bstract Gray seals ( Halichoerus grypus ) in the UK exhibit clear preferences for pupping close to pools of water on inland breeding sites. The reasons for this are unclear as seals are thought to derive all their water requirements from the metabolism of fat. Likewise, the prospect of seals overheating during the UK's cool, damp, autumnal breeding seasons, has seemed unlikely, but has not been previously explored. Here, we provide preliminary behavioral evidence of thermal stress in female gray seals breeding on the island of North Rona, Scotland. Video footage provided measures of proximity to, and the proportion of animals bathing in, pools in relation to meteorological data (temperature, mean sea‐level pressure, rainfall, wind speed and direction) on four dates spread through a single breeding season. The proportion of females close to pools increased with pressure (warmer, drier conditions) and decreased on wetter days. In addition, analyses of colony‐wide patterns of seal dispersion showed that females tended to be closer to pools of water at higher pressures and temperatures and at lower wind‐speeds. These results provide the first evidence of thermal stress and behavioral thermoregulation through access to pools of water in a phocid breeding in temperate autumnal conditions.

Male short-tailed field voles ( Microtus agrestis ) build better insulated nests than females - P. Redman; C. Selman; J. R. Speakman (Journal of Comparative Physiology B, 1999)